2003
DOI: 10.1093/ps/82.2.279
|View full text |Cite
|
Sign up to set email alerts
|

The relation between starch digestion rate and amino acid level for broiler chickens

Abstract: Digestion coefficients of nutrients give information about the amount of nutrients available to the animal but not about the rate or site of absorption. Gradual digestion of starch may have an amino acid sparing effect and therefore enhance growth efficiency of broiler chickens. A growth trial was performed with 6,800 broiler chickens from 9 to 30 d of age to investigate interactions between starch digestion rate and amino acid level. Birds were fed either a pea-corn-based diet (slowly digestible starch) or a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 7 publications
4
37
1
Order By: Relevance
“…The performed trial revealed a positive Pearson's correlation between starch concentrations in pea seeds and ileal digestibility of nearly all amino acids (average r = 0.60; P ≤ 0.05). According to Weurding et al (2003), due to its structure, pea starch is characterized by very slow degradation in the gastrointestinal tract of birds compared with maize starch. The above authors speculated that diets with rapidly digestible starch may result in elevated plasma glucose levels when other nutrients are not yet absorbed, which may have consequences for protein utilization (Weurding et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The performed trial revealed a positive Pearson's correlation between starch concentrations in pea seeds and ileal digestibility of nearly all amino acids (average r = 0.60; P ≤ 0.05). According to Weurding et al (2003), due to its structure, pea starch is characterized by very slow degradation in the gastrointestinal tract of birds compared with maize starch. The above authors speculated that diets with rapidly digestible starch may result in elevated plasma glucose levels when other nutrients are not yet absorbed, which may have consequences for protein utilization (Weurding et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…According to Weurding et al (2003), due to its structure, pea starch is characterized by very slow degradation in the gastrointestinal tract of birds compared with maize starch. The above authors speculated that diets with rapidly digestible starch may result in elevated plasma glucose levels when other nutrients are not yet absorbed, which may have consequences for protein utilization (Weurding et al, 2003). The higher amino acid AID in the cultivars characterized by higher starch contents determined in the current study is difficult to explain and needs further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower feed intake of diets containing extruded corn might explain the poorer weight gain observed (Johnston et al, 1999). Weurding et al (2003) and Van Kempen et al (2007) also reported that raw corn was preferred for animal feeding due to its slowly digestible starch resulting in a slow and steady release of glucose which did not strongly stimulate insulin, therefore raw corn could improve feed intake and performance. In addition, the reason for the lower feed intake in extruded corn may be due to the poorer palatability caused by higher levels of retrograded starch (Hongtrakul et al, 1998;Lv et al, 2006) compared with raw corn.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that the provision of some slowly digestible starch in broiler diets is beneficial for feed conversion efficiency [79][80][81]. One possibility is that retarded starch digestion rates provide a greater supply of glucose to the lower small intestine which spares amino acids from catabolism for energy to meet the gut mucosa's requirements thereby permitting the entry of amino acids into the systemic circulation to become available for protein deposition [22].…”
Section: Starch and Protein Digestive Dynamics In Sorghum-based Broilmentioning
confidence: 99%